Azotobacter and Azospirillum Inoculants for Nitrogen Economy in Vegetable Cultivation - Arunkumar S (Department of Plant Pathology, College of Agriculture, 1997)
The study on Azotobacter and Azospirillum inoculants for nitrogen economy in vegetable cultivation was conducted at College of Agriculture, Vellayani, Thiruvananthapuram during 1994-1996. Two sets of experiments consisting of pot and field trials were conducted for this purpose. Pot culture experiments with amaranthus showed that, plant height, root biomass, leaf area index and yield were significantly high in the treatment combination of Azospirillum inoculation along with FYM and 75 percent fertilizer nitrogen (N3FYM+AS). Flowering time was also significantly delayed in this treatment. Among Azotobacter treatments also plant height, leaf area index and yield were significantly high in the treatment receiving 75 percent nitrogen along with FYM and Azotobacter inoculation (N3FYM+AB). In brinjal while Azospirillum inoculation along with 75 percent nitrogen and FYM (N3FYM+AS) could significantly increase yield and